Simultaneous observation of transient and final state dynamics in ultrafast strong-field excitation via time-resolved photoelectron spectroscopy. Issue 10 (17th June 2017) - Braun, Hendrike; Bayer, Tim; Pengel, Dominik; Wollenhaupt, Matthias; Baumert, Thomas
Abstract : Strong-field coherent control deals with the efficient excitation of a quantum system into a preselected final state. In order to understand the underlying control mechanisms, the transient dynamics of the laser-dressed states need to be considered in addition. In this paper, we present a route towards a complete picture of non-perturbative coherent control. To this end, we study near-resonant chirped excitation of potassium atoms as a model system for resonant strong-field control. Combining a two-colour pump–probe scheme with photoelectron spectroscopy, we simultaneously observe final state and transient excitation dynamics in the strongly driven atom. As demonstrated on the prototype scenario, the scheme enables a detailed understanding of the physical mechanisms governing the interaction. Our results highlight the power of two-colour time-resolved photoelectron spectroscopy to shed light onto the different aspects of non-perturbative coherent control.